Integrated Pedagogical Roles of Biology Teachers in Addressing Learning Barriers in a Pesantren-Based Secondary School (LITPAM, 2025)
This study examines how biology teachers at SMAS Darul Falah Mataram address learning challenges in a pesantren-based secondary school environment marked by religious routines and resource limitations. It identifies critical gaps in instructional approaches and emphasizes the need for holistic teacher roles. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis. Thematic findings reveal three primary roles enacted by teachers: (1) educators who model discipline and ethics, (2) instructors who use contextualized and remedial teaching, and (3) mentors who foster emotional and cognitive engagement. These roles collectively address both academic deficiencies and character development. The study’s implications underscore the importance of embedding multidimensional teaching strategies in teacher training and school policy frameworks, particularly for religious or high-pressure educational contexts.